Effect Of Nitrogen For Yield Maximization Of Garlic In Old Brahmaputra Flood Plain Soil - Zaman, MS; Hashem, MA; Jahiruddin, M; Rahim, MA (Bangladesh Journal of Agricultural Research, 2011)
The experiment was conducted for two consecutive rabi seasons of 2005-06 and 2006-07 at the Regional Agricultural Research Station (RARS), Jamalpur to find out an optimum dose of nitrogen for the production of garlic (cv. Jamalpur local). There were six levels of nitrogen viz., 0, 50, 100, 150, 200, and 250 kg/ha. The experiment was laid out in randomized complete design with three replications. Results revealed that nitrogen had significant effects on almost all the parameters studied. Nitrogen @150 kg/ha produced the highest bulb yield (6.75 t/ha in 2005-06 and 7.19 t/ha in 2006-07) and there was a reduction of yield with further increment of nitrogen level. The control treatment receiving no fertilizer produced the lowest bulb yield in both the years. The yield benefit for 150 kg N/ha was 40% than the yield obtained from nitrogen control treatment when average of two years’ yield is considered. Keywords: Nitrogen; garlic; growth; bulb yield. DOI: http://dx.doi.org/10.3329/bjar.v36i2.9263 BJAR 2011; 36(2): 357-367